Tourism Development and the Livelihood of Local People in Dhorpatan, Baglung, Nepal - Panta, Saroj Raj; Silwal, Sudarshan; Baral, Ramchandra; Paudel, Mohan Kumar; Panta, Suveksha (Dhaulagiri Journal of Contemporary Issues, 2026)
The major aim of this study is to analyse how tourism influences the way of life for residents of Dhorpatan, Baglung. And it also identify the livelihood of people in Dhorpatan. Tourism has become a central component of rural livelihood transformation in Dhorpatan. Widely recognized for the Dhorpatan Hunting Reserve, it is Nepal’s only hunting reserve, the region has experienced gradual growth in domestic trekking, hunting tourism and community-based hospitality services. This study employed a convergent mixed-methods design to assess how tourism influences household income, employment, gender roles and socio-economic resilience. Quantitative data were collected from 160 participants through structured surveys. Qualitative insights were gathered from key informant interviews, focus group discussions and case studies. Findings indicate that the households derive partial income from tourism-related activities with tourism contributing to livelihood for income among participating families. Tourism has enhanced income diversification, promoted women’s entrepreneurship in homestays and reduced seasonal labour migration. However, the benefits are unevenly distributed because of its infrastructural deficits, seasonal fluctuations and limited community access to hunting reserve revenues. The study concludes that tourism significantly contributes to livelihood improvement in Dhorpatan. Yet sustainable and inclusive governance mechanisms are essential to maximise equitable local benefits. This study will be fruitful for future researchers, students and local bodies to prepare a plan for its betterment.